Patterned Ion‐Pair Membrane for High‐Temperature Proton‐Exchange Membrane Fuel Cells - Sanghyeok Lee; Songi Oh; Sohee Kim; Jinyeong Lee; Wonhyeong Lee; Katie Heeyum Lim; Ji‐Hoon Jang; Segeun Jang (Small Structures)
Despite the many advantages of catalyst‐coated membranes (CCMs), there have been few studies of the use of CCMs to construct membrane‐electrode assemblies (MEAs) for high‐temperature polymer‐electrolyte membrane fuel cells (HT‐PEMFCs) using phosphoric acid (PA) doping. In this article, the use of membrane patterning to enable CCM to be utilized for HT‐PEMFCs is reported. A PA‐doped ion‐pair membrane and an electrode containing protonated phosphonic acid ionomers are employed to fabricate CCMs using the direct‐decal‐transfer method. A membrane with an inverted‐pyramid structure, created using solvent‐assisted patterning, further exploits the advantages of CCMs. The resulting CCM exhibits improved decal‐transfer efficiency, increased capillary infiltration of PA, and reduced PA loss during compression. The enlarged, interlocked, 3D structure increases the interfacial adhesion strength and the electrochemically active surface area compared to a conventional MEA with either a catalyst‐coated substrate or a flat CCM. Due to the morphological modification of the electrode, the patterned CCM also exhibits the lowest oxygen‐transport resistance among the MEAs. As a result of these enhancements, the patterned CCM achieves the high performance of 680 mW cm−2 at 160 °C in dry H2/air with low total Pt usage of 0.5 mg cm−2.